Diseño de una finca agroecológica bajo los principios de territorios de producción limpia en la parroquia Chicaña, cantón Yantzaza - Torres Jiménez, Cristian Alonso (2015)
The agricultural models developed in the mid-twentieth century that promoted a conventional production system, which have been proved unsustainable, since today we face an environmental, social and economic crisis. Viewing this the Autonomous Decentralized Government of Zamora Chinchipe, has taken action that contribute to achieve greater harmony between the productive activities and the environment, through the enactment of an ordinance that regulate the building of the Territories of Cleaner Production (TCPs); However there is not demonstrative scenarios at the field level in which have been comprehensively implemented the principles and criteria TCPs. For that reason, in this project it is proposed the implementation of a model farm that fulfills each of the criteria and principles set in the ordinance. For the development of the present work, it was begun with the participative diagnosis, which consists of two phases, the first, is the recognizing of the place and the elaboration of the base map and the second is the participative diagnostic based on the criteria and principles TCPs. Then taking as a reference the obtained results it was preceded to the development of the management plan for the farm, which fulfills to each of the criteria and principles of Cleaner Production Territories